IMPLEMENTASI PENERAPAN PENGKREDITAN PAJAK MASUKAN BAGI PENGUSAHA JASA PENYEDIA JALAN TOL UNTUK MEWUJUDKAN KEPASTIAN HUKUM - Guritno, Yulianto (Universitas Nasional, 2022)
Value Added Tax is a tax that can be categorized as an objective tax. Value Added Tax is also called Indirect Tax, this is because the burden of the tax can be delegated to other parties. Value Added Tax is regulated in Law no. 42 of 2009 concerning Value Added Tax, the Law regulates the existing policies in each Value Added Tax Object. The research objectives in writing this are to analyze and develop the rules and implementation of toll road VAT collection in Indonesia and to analyze the legal certainty of crediting input tax on toll roads for toll road service entrepreneurs in Indonesia. The research uses a normative juridical approach that emphasizes library research. In this study, the legislation approach, conceptual approach, comparative approach, case approach, and historical approach are used.Based on the results of the study, it shows that the VAT regulation is regulated inLaw Number 8 of 1983 concerning Value Added Tax of Goods and Services and Sales Tax on Luxury Goods as amended by Law Number 18 of 2000 (hereinafter referred to as the VAT Law) stipulating that: Article 1 number 25: Output Tax is a Value Added Tax payable that must be collected by a Taxable Entrepreneur who delivers Taxable Goods, delivers Taxable Services or exports Taxable Goods. Article 4A paragraph (3) along with its explanation, toll road provision services are not included in the group that is not subject to Value Added Tax. Article 9 paragraph (2) Input Tax in a Tax Period is credited with Output Tax for the same Tax Period. Article 16B paragraph (2) Input Tax that is paid for the acquisition of Taxable Goods and or the acquisition of Taxable Services for which Value Added Tax is not collected can be credited